Analysis Of Differences In Student Learning Outcomes In Educational Research Courses Using The Arias Learning Model (Assurance, Relevance, Interest, Assesment, Satisfaction ) - Setyawan, Trinovandhi; Kusmawati, Wiwik; Budijanto, Budijanto; Ernata, Yusvidha; Irawan, Dedy; Nuh, Fuad Azhar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The aim of this research is to determine differences in student learning outcomes in Educational Research courses using the ARIAS learning model. The research method is a quasi-experimental method. The sampling technique was simple random sampling. The sample is students from Class 2021 class F as the experimental class and students from Class 2021 class G as the control class. The data collection technique uses tests and non-tests. The instruments are objective tests of the multiple choice type and non-test instruments in the form of questionnaires. The data obtained were analyzed using the prerequisite normality test and homogeneity test. The results of the t-test carried out using the SPSS program showed that the tcount value was greater than the ttable value, meaning that there was a significant difference in the learning outcomes of students in the experimental class and the control class, so it could be concluded that there was a difference in student learning outcomes in the Educational Research course. using the ARIAS learning model.